VAT multipliers and pass-through dynamics - Simon Voigts (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
To quantify fiscal multipliers in Eurozone countries, ECB, European Commission, and IMF draw heavily on large-scale DSGE models. In these models, the value added tax (VAT) is represented by a consumption tax, implying that changes in the tax liability directly translate into changes in consumer prices. This is inconsistent with empirical evidence suggesting that VAT pass-through in Europe is only gradual. To study the implications of this shortcoming for VAT multipliers, I derive a DSGE model featuring both a consumption tax and a VAT with pass-through dynamics consistent with empirical evidence. Short-run multipliers from the consumption tax are dramatically larger than those from the VAT, which suggests systematic overestimation in institutional research.
Keywords: E62; 330; Fiscal multipliers; value added tax; tax pass-through; DSGE models